Are we telephoning ourselves to an upcoming danger? - Sreenivasulu Pattipati; Ragha Geethika Velugubantla; Praveen Kumar Balmuri; Ramaswamy Pachigolla; Tanya Khaitan; Uday Ginjupally (Wolters Kluwer Medknow Publications, 2015)
Aims and Objectives: To evaluate the effect of mobile phones on salivary flow rate and protein concentration in parotid saliva by comparing the dominant and non-dominant sides of prolonged mobile phone users. Materials and Methods: Parotid saliva was collected simultaneously from both the glands in 50 healthy volunteers by using sialographic cannula. The obtained results were statistically analyzed using paired t-test. Results: Salivary secretion rate was significantly less on the dominant side of mobile phone usage. There was no such significance in protein concentration on comparing the dominant side with the non-dominant side. Conclusion: It was concluded that there was a change in the functional activities of the parotid gland in prolonged mobile phone users.